Synergistic Effect of Purified Protease Enzyme with Antibiotics on Pathogenic S. Aureus In-Vitro and In-Vivo - Abdulwahhab, Haifa Sadoon; Khalaf, Khawlah Jebur; Aziz, Raghad Akram (Journal of Contemporary Medical Sciences, 2024)
Objective: The goal of this study is the detection of the P. aeruginosa isolate for production the protease, the optimal conditions for produce, extraction, purification and characterization of the enzyme and study the synergistic effect of protease with antibiotics on S. aureus. Method: Among (110) isolates from clinical sources, only (74) isolates identified as P. aeruginosa isolated from Baghdad hospitals. Detection of the optimal isolate for production the protease enzyme and the optimal conditions its produce, purification of enzyme by using ammonium sulfate, ion exchange chromatography and gel filtration, enzyme characterization of PH and temperature activity and stability, the study of synergistic effect of protease with antibiotics on S. aureus. Results: The optimal conditions to produce protease is pH (8), (37) ºC, (BHI) broth, and during (48 hrs.). The precipitation saturation ratio (80%). Ion- exchanges (DEAE and CM) Cellulose and Gel filtration have specific activity ((121.25), (161.6), (660.53)) units/ mg)) respectively. The characterization done by pH and temperature activity purified protease was active in (138.51units/ ml) at pH (8), and stable in pH (8), the temperature for protease activity is (158.21 units/ ml) at (37) ºC. The synergistic effect of purified protease with antibiotics on S.aureus in- vitro,was detected using the agar diffusion method, the effectiveness of the prepared hydrogel types, the results showed S.aureus was more sensitive isolate to prepare (Gel & Protease & Ceftriaxone) the diameter of the inhibition zone reached (44 mm) ,the synergistic effect we noticed when using a (Gel & Ceftriaxone & Protease) healing was observed in time (five days) with wound healing without effect. Conclusion: In this study, it was discovered that mixing (protease + hydrogel + Ceftriaxone) accelerates the wound healing without leaving traces.